Rinoneumonitis equina en Chile (1969 -1992) - Berríos, E. (Avances en Ciencias Veterinarias, 1992)
In this general article is presented the situation of equine rhinopneumonitis in Chile from 1969, when a long and heavy outbreak of abortion occurred at the Central Zone of the country, causing serious losses in thoroughbred. After a program of immunization iniciated in 1974 by using a modified live vaccine (Rhinomune), equine rhinopneumonitis decreased gradually. Equine herpes virus type 1 was isolated from liver of aborted fetuses and nasal or ocular discharges of sick adult horses. In 1984 the virus was isolated again from aborted fetuses belong to Victoria, IX Region of Chile; this is the only case of equine rhinopneumonitis described at the south of the country. Moreover, different studies were done about the use of complement fixation test, viral seroneutralization, passive haemag glutination test and direct fluorescent technique to diagnose equine rhinopneumonitis; adaptation of the virus in guinea pigs and post vaccinal response to modified and inactivated vaccines against this disease. Finally it is discussed the current situation of equine rhinopneumonitis in Chile. Key words: Virus, equine rhinopneumonitis, horses.Palabras claves: Virus, rinoneumonitis equina, quinos.